The Relationship Between Interpersonal Victimization and Women's Criminal Sentencing: A Latent Class Analysis. Issue 3 (27th May 2018) - Kennedy, Stephanie C.; Mennicke, Annelise M.; Feely, Megan; Tripodi, Stephen J.
Abstract : Latent class analysis was used to identify subgroups of incarcerated women differentiated by experiences of child abuse and intimate partner violence victimization. The abuse subscales of the Childhood Trauma Questionnaire and the Abuse Behavior Inventory were used as indicators. Data were drawn from a probability sample of 217 incarcerated women housed in two state-level prisons in North Carolina. Four classes were extracted—Low Victimization, Child Abuse, Lifetime Physical and Psychological Abuse, and Lifetime Sexual Abuse; classes were then related to current sentence length, holding criminological predictors constant. Women in the Child Abuse and Lifetime Sexual Abuse classes had significantly longer sentences, despite the lack of significant between-class differences on criminological predictors. Results suggest that certain victimization patterns, notably experiences of sexual violence, were associated with sentencing disparities despite the use of structured sentencing grids. Recommendations for trauma-informed sentencing are provided.